An investigation into the performance of counter rotating floating ring journal under different working conditions - Abass, Basim A.; Alwan, Adel A.; Hunain, Mustafa B. (Al-Khwarizmi Engineering Journal, 2007)
The steady state performance of the counter rotating floating ring Journal bearing is analyzed with isothermal finite bearing theory. The effect of different parameters affecting the performance of the bearing (namely speed ratio, clearance ratio and radii ratio), have been investigated. The load carrying capacity of the bearing increasing with decreasing the radii ratio (R2/R1) of the ring and clearance ratio (c1/c2), in the other hand, the coefficient of friction increases with increasing the clearance and radii ratios, while decreases with incre4asing the bearing to journal speed ratio (γ). It is shown during this work that different operating conditions are greatly enhanced the performance of such bearings.